Hellp syndrome- pre-eclampsy complication: An experience report - Bastos, Pâmela Souza (2021)
Objective: To describe the assistance provided to women with Hellp Syndrome. Methodology: This is a study of a descriptive character and qualitative nature in the experience report modality. However, the research was carried out from the experience of a student of the Bachelor of Nursing course, during the internship, held in a hospital located in the interior of Bahia. Results: Pregnant women with pre-eclampsia and gestational hypertension were classified in red, for those with seizures or labor in expulsive period, orange for those with blood pressure >140x100 mmHg, with epigastric pain and scotoma headache, and blood pressure >160x100 mmHg, and this classification is performed by the nurse. During the care of a serious pregnant woman, it was possible to identify pregnant women with pre-eclampsia who were not followed up in high-risk prenatal care, and even being attended to in low-risk prenatal care, they did not use antihypertensive drugs to control their blood pressure levels. Conclusion: It is evident that there are still lapses related to the treatment of pregnant women with Hellp syndrome, since this complication does not have a concrete pathophysiology, and which is considered by researchers in the area of ​​obstetrics as a complication of severe pre-eclampsia.